2022
DOI: 10.5380/reterm.v21i2.87921
|View full text |Cite
|
Sign up to set email alerts
|

Exergetic Analysis of an Internal Combustion Engine Running on E22 and E100

Abstract: The internal combustion engine performance enhancement is a widely explored subject. Additionally, to pollutant emissions attention, reducing fuel consumption and consequently the greenhouse gas emissions is one of the leading research and development drivers for the future of the engines industry. As the technologies to increase global engine efficiency are becoming less promising (already reaching improvement limits), the next round would be developing technologies capable of recovering the energy rejected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Maximum engine efficiencies with recovery potential were about 50% and 46% for the WOT and POT conditions, respectively, at 3000 rpm. These values of the second law efficiency under the WOT operating condition are within the range of the previously recorded data, i.e., 53%, 45.62 and 53.6%, as stated by [26,27,44], respectively. In another work presented by [15], it was reported that the total exergy efficiency could be substantially enhanced by up to 60% based on recuperating both the cooling water and exhaust gas energies.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Maximum engine efficiencies with recovery potential were about 50% and 46% for the WOT and POT conditions, respectively, at 3000 rpm. These values of the second law efficiency under the WOT operating condition are within the range of the previously recorded data, i.e., 53%, 45.62 and 53.6%, as stated by [26,27,44], respectively. In another work presented by [15], it was reported that the total exergy efficiency could be substantially enhanced by up to 60% based on recuperating both the cooling water and exhaust gas energies.…”
Section: Resultssupporting
confidence: 88%
“…These results were interpreted mainly due to the high fuel consumption rate and the blended fuels' low energy content. An exergtic analysis of an ICE running on twoboundary Brazil flex-fuels, including gasoline blend and hydrous ethanol performed by [26]. Hydrous ethanol produced 4.5% higher energetic efficiency than gasoline blend for the same engine configuration due to superior fuel properties.…”
Section: Introductionmentioning
confidence: 99%
“…In the final part of the representation, there are indications of enthalpy losses to the environment from exhaustion flue gases (ICEV), exergy transfer to the environment associated with heat, and other exergy losses associated with friction, fuel, the batteries, and the tank. The energy and exergy analyses of these processes are based on previous studies by Fusco and Mady [27].…”
Section: Methodsmentioning
confidence: 99%
“…The traction force work is calculated by gathering traction force and integrating it as a function of distance between two interval points. Then, lost work (destroyed exergy) can be calculated by fuel exergy (chemical exergy), exhaust gas exergy (thermal exergy), and exergy related to heat exchanged between the engine and the vehicle's surroundings [27]. Unlike the authors, our system's frontier is considered the environment.…”
Section: Thermodynamicsmentioning
confidence: 99%
See 1 more Smart Citation